The economics of the distributive trades - McAnally, Patrick (London : Allen and Unwin, 1971)
It is a theoretical book on a practical subject, and should perhaps commend itself automatically to those with a theoretical turn of mind. Furthermore, the meaning of marketing shall be explained later, is a popular field of study, but the wider field of distribution is not. Whether this comparative neglect by the theoretically minded is justified will become more apparent, as the author pursues the subject.
Includes bibliographical references and index.
II 15/01/2019
Loans
Keywords: Retail trade; Commerce